Strengthening the Spirituality of Lenten Repentance Based on Synodal Journey in Realizing the Transformation of the Life Orientation of Church Ministers in the Diocese of Bangka-Belitung - Alfonsus Ara (Abdimas Paspama, 2023)
Lent is a momentum of renewal that directs the people to change their orientation in life from self-interest to a deeper relationship with God, others, and the mission of the Church. This Community Service activity aims to strengthen the spirituality of Lent repentance based on synodal journeys for Church servants in the Diocese of Bangka-Belitung in the context of the Year of Thanksgiving of the Diocese of Pangkalpinang. The activity was held on Tuesday, March 14, 2023 in Parittiga, West Bangka Regency, Bangka-Belitung Islands, and was attended by 39 participants consisting of 27 diocesan priests, 3 religious priests, 1 deacon, and 8 brothers. The activity methods include theological-interactive presentations, personal reflection, synodal dialogue, deepening of ministry experiences, and worship. The validity of the implementation is verified through assignment letters, attendance lists, event minutes, and resource person certificates. The results at the process level show the availability of structured reflection space, the strengthening of the understanding of the relationship between metanoia and communion-participation-mission, and the strengthening of a more dialogical and responsible ministry orientation. This article does not use pre-test and post-test scores because the implementation document does not contain these instruments; Quantitative analysis is limited to verifiable attendance data. This model of recollection is relevant as a form of ongoing coaching because it integrates theological foundations, pastoral experiences, community dialogue, and follow-up recommendations.